Anaerobic co-digestion of food waste and brown water - Leong, Yuan Shan. (2011)
Anaerobic digestion technology is one of the sustainable approaches to convert wastes into a biogas that provides a renewable energy source to replace the diminishing non-renewable natural resources. This research was mainly to study the performance of anaerobic co-digestion of food waste and brown water at different organic loading ratios. Monitoring parameters include the measurement of pH, volatile solids reduction, chemical oxygen demand (COD), alkalinity, volatile fatty acids (VFA) concentration, biogas composition, methane yield, and methane production rate. The experiments were conducted at a temperature of 35°C. The organic loadings for the anaerobic digestion of food waste and brown water were 0.3gVS/L, 0.5gVS/L, 1.0gVS/L and 2.5gVS/L. Both digestions had shown decreased pH and increased VFA concentration in the initial phase of the digestion. Smaller organic loadings yielded higher methane gas for every gram of VS added to the both systems, while higher organic loadings had higher methane yield per gram of VS or COD removed. 80% of methane yield per VSadded for both digestions had been achieved in the first 10 days, with methane contents in the range of 50-80%. Low pH and VFA accumulation may be the result of inhibition of the methanogens, affecting the methane yield. Food waste yielded lesser methane than brown water, with likelihood of inhibition effects due to high oil content in the food waste. Based on the digestion of food waste and brown water, co-digestion was conducted with the organic loading ratios of 0.5:0.5, 0.3:0.7, 0.7:0.3 and 1:1 brown water versus food waste. Either combinations of 0.3gVS/L of food waste and 0.7 gVS/L of brown water or 0.7gVS/L of food waste and 0.3 gVS/L of brown water yielded halved as much as the digestion of the substrates individually. As for the 0.5gVS/L and 1.0gVS/L loadings, co-digestion also yielded lesser methane than individual digestion. The results suggest that co-digestion failed to improve methane production rates and that the anaerobic digestion of food waste and brown water are incompatible. It could be due to microbial interactions of the microorganisms from both substrates when they were mixed such as amensalism where either one microbial population caused inhibitory effects to the other population, or due to chemical reactions of fermentation by-products of food waste and brown water digestion. Further studies recommended include the explicit study on the microbial interactions of food waste and brown water in municipal sewage sludge, and the chemical reactions pathway of co-digestion of food waste and brown water.